Pancasila Student Profile Dimensions of Critical Reasoning through Differentiation Learning in the Context of Independent Learning - Hardiany, Desi; Rif'at, Mohamad; Siregar, Nurfadilah; Jamiah, Yulis; Hartoyo, Agung (Budapest International Research and Critics University, 2024)
This research aims to describe a study of the profile of Pancasila students who reason critically through differentiated learning on circle material in class VIII of SMP Negeri 9 Simpang Hilir. The method used is qualitative research in descriptive form, involving class VIII A students. Data was collected through observation, questionnaires and tests. The results of the research show that the results of the learning style test of class VIII A students before differentiated learning show a diversity of students' learning style preferences: 10 people are kinesthetic, 3 people are auditory, and 7 people have a combination of two learning styles, namely 1 visual kinesthetic, 3 visual kinesthetic, 2 visual auditory, and 1 auditory visual. Preliminary test results show that the average critical reasoning ability score of class VIII A students is 57.6, which is in the